1987
DOI: 10.11150/kansenshogakuzasshi1970.61.1141
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Isolation of the Two Specific Strains of Str. sanguis from Tooth Plaques Among the Patients with MCLS

Abstract: Two specific strains of Str. sanguis were isolated from tooth plaques in 61.7% of the patients with MCLS and their mothers, while the incidence among 744 controls was 1.9%. Serum indirect hemagglutination inhibition test, assayed by using sensitized sheep RBC with superficial antigen of the strains, showed a maximal increase in titers at 2 to 3 weeks of the disease course, followed by a gradual decrease. Injections of these strains, the filtrate and the purified component of the bacterial culture broth each ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The patients show hypersensitivity in skin tests with streptococcal antigens, and sometimes symptoms typical of BD are provoked by an injection of these antigens (16). We found that the proportion of Streptococcus sanguis in the oral flora of BD patients significantly increased as compared with the controls and that the antigenicity of S. sanguis strains isolated from BD was different from that of the three type and reference strains of ATCC (ATCC10556T, ATCC10557, and ATCC10558T) as well as the S. sanguis strains isolated from patients with Kawasaki disease (designated as MCLS-1 and MCLS-2) (9,15 (3). They found that the cultures which were considered to be S. sanguisfrom their biochemical properties could be divided into two genetic groups (groups 1 and 3).…”
mentioning
confidence: 89%
“…The patients show hypersensitivity in skin tests with streptococcal antigens, and sometimes symptoms typical of BD are provoked by an injection of these antigens (16). We found that the proportion of Streptococcus sanguis in the oral flora of BD patients significantly increased as compared with the controls and that the antigenicity of S. sanguis strains isolated from BD was different from that of the three type and reference strains of ATCC (ATCC10556T, ATCC10557, and ATCC10558T) as well as the S. sanguis strains isolated from patients with Kawasaki disease (designated as MCLS-1 and MCLS-2) (9,15 (3). They found that the cultures which were considered to be S. sanguisfrom their biochemical properties could be divided into two genetic groups (groups 1 and 3).…”
mentioning
confidence: 89%
“…In these strains, 2 were isolated from Kawasaki disease patients and 4 strains were isolated from Beh(;et patients, and these strains have been suspected to be causative of the diseases, although decisive data have not yet been obtained (9,13,14,16,18,20,25,28). Interestingly, these 6 strains were slightly different in nature from ordinary S. sanguis isolates (9,16,28) and were rarely isolated. A previous article demonstrated that tachyplesin I inhibited the growth of E. coli and Salmonella typhimuriitm bactericidally (21).…”
Section: Discussionmentioning
confidence: 99%
“…Table I shows the susceptibility of various streptococcai strains to tachyplesin I. Four 5. sanguis strains were highly susceptible and 8 strains were moderately susceptible, whereas 9 strains were highly resistant to tachyplesin I. Atnong resistant strains, MCLS-1 and -2 were isolated frotn Kawasaki disease patients and KTH 1, 2, 3 and 4 were isolated from Behpet's syndrome patients (9,14,16,18,28). These strains have been investigated with special reference to the diseases.…”
Section: Time-kill Studymentioning
confidence: 99%